Efficacy of Disulfiram for the Treatment of Alcohol Dependence Assessed with a Multicenter Randomized Controlled Trial. (11th October 2013) - Yoshimura, Atsushi; Kimura, Mitsuru; Nakayama, Hisakazu; Matsui, Toshifumi; Okudaira, Fukiko; Akazawa, Shigeru; Ohkawara, Masao; Cho, Tetsuji; Kono, Yoshihiro; Hashimoto, Koji; Kumagai, Masayuki; Sahashi, Yukiko; et al.
<x xml:space="preserve">Abstract</x> Background The efficacy of disulfiram in preventing an alcoholic relapse has been controversial. The aim of our study was to assess the efficacy of supervised disulfiram for the treatment of alcohol dependence with a multi‐institutional study in Japan. Methods In a single‐blinded, randomized placebo‐controlled study, we recruited 109 patients diagnosed with alcohol dependence under ICD‐10 criteria. The patients were randomly allocated to 4 treatment groups, depending on whether they took disulfiram (200 mg daily) or a placebo or whether they received adjunctive therapy consisting of mailed letters which delineated and emphasized the harmful effect of alcohol and the management of alcohol craving. The proportion of abstinence among the 4 groups at 26 weeks after discharge was the primary outcome measure. The proportion of abstinence was compared with the severity of alcohol dependence and craving. Furthermore, we examined the proportion of abstinence in patients with inactive aldehyde dehydrogenase‐2 (ALDH2). Results There were no significant differences among the 4 groups in terms of abstinent patients or study dropouts. The ratio of abstinence was not related to the severity of alcohol dependence or the degree of alcohol craving. Patients with inactive ALDH2 significantly sustained abstinence with the use of disulfiram (p = 0.044). Conclusions Supervised oral disulfiram use followed by intervention via letters seems to be ineffective for increasing abstinence. Further studies are necessary to prove the efficacy of disulfiram for the pharmacological treatment of alcohol dependence. We indicated the effectiveness of disulfiram for the maintenance of abstinence in patients with inactive ALDH2.